Quantifying Aquaculture-derived Dissolved Organic Matter in the Mesocosms of Sanggou Bay Using Excitation-emission Matrix Spectra and Parallel Factor Analysis - XiaonaWang and Ying Wu; Zengjie Jiang; Qianqian Ma and Jing Zhang; Sumei Liu (World Aquaculture Society, 2025)
The cycling and fate of dissolved organic matter (DOM) in aquaculture systems are unique. Sanggou Bay, an aquaculture-dominated system in China, was chosen to characterize the composition of DOM based on optical properties. Field incubation experiments of eight mesocosms containing various aquaculture organisms were conducted in July 2013 to explore the impact of aquaculture organisms on the DOM composition. Dissolved organic carbon (DOC) showed an increasing trend, especially in integrated mesocosms, suggesting the accumulation of DOM in the aquaculture ecosystem. The DOC concentration was positively correlated with a280 (P < 0.01) rather than a355, demonstrating that a280 should be applied in the quantitative prediction of DOC in aquaculture systems. Parallel factor analysis was applied to identify the components of the excitation-emission matrix spectra. Two humic-like components and two protein-like components were identified. The significant correlation between the wet weights of the organisms and the humic-like component contents (P < 0.01) indicated that seaweeds and bivalves play important roles in the production of humic-like matter. The variation of protein-like materials was caused by the growth of aquaculture organisms and the decay of phytoplankton. The amount of bioavailable DOC (BDOC) derived from phytoplankton and organisms was estimated; bivalve organisms excreted more BDOC than did seaweeds. BDOC was significantly correlated with the protein-like components (P < 0.05) in the microbial incubation experiment.